Experience and education in social field. Elements of analysis in a Freirian perspective - Piergiorgio Reggio (University of Bologna, 2017)
The article deals with the link between social dimension and educational action. First of all, the text addresses the actual crisis of the social dimension in the conditions of everyday life. The social dimension is consumed by the expansion of the political sphere, and of the private one. In order to rethink the educational work in the social contexts, it is necessary to adopt a critical perspective that - in the specific - is identified  as  the contribution of Freirian pedagogy. The latter is traditionally carachterized by a clear orientation towards personal, social and political change. In the Freirian perspective, the education consists in the process of "conscientization", that is the development of critical awareness, and adopts ways of "problematization" and dialogue. The meaning of experience, and the fundamental principles of the Experiential Learning approach - that  employ original contributions of the Freirian pedagogy - are, finally, assumed as basis  for strategies and educational actions in the social dimension.